Future of Work in the Gastronomy Sector: Challenges of Adopting Artificial Intelligence in a Service Industry - Sardogan, Abdullah; Wirsam, Jan; Alt, Rainer (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
The digital transformation and Artificial Intelligence (AI) integration promise to restructure complex service operations from back-stage management to front-stage customer interactions. However, while theoretical benefits of automation and augmentation are recognized, practical implementation in gastronomy frequently stalls, overlooking specific socio-technical realities of physical environments. To address this gap, we conducted a qualitative, exploratory study based on expert interviews (N=6) using a dyadic sample of AI providers and gastronomy operators. Findings indicate that AI integration is rarely hindered by algorithmic flaws but collides with a multi-layered socio-technical integration gap: (1) unstandardized analog processes preventing deterministic data extraction, (2) infrastructural debt from legacy IT, and (3) monopolistic vendor politics enforcing lock-ins and stifling scalability. This paper contributes to the Future of Work discourse by demonstrating that algorithms cannot optimize fragmented physical workflows, highlighting process standardization, workflow virtualization, and open data standards as critical prerequisites.